Clinicopathological features of trichoblastomas and malignant variant: trichoblastic carcinoma - CİNEL, ZELİHA LEYLA (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Trichoblastomas are rare benign tumors of the skin appendages with epithelial and mesenchyntal components that exhibit differentiation to the follicular germinative epithelium and particularly to the follicular stroma of the skin. Our aim was to contribute to already limited literature data in order to gain more insights into the treatment and follow-up of patients with this condition. Methods and Materials: A total of 9 patients with trichoblastoma and 1 patient with malignant trichoblastoma were surgically treated between 2016 and 2020 at the Department of Plastic, Reconstructive and Aesthetic Surgery, School of Medicine, Marmara University. Results: Of the 10 patients with trichoblastoma, 5 were female and 5 were male, with a median age of 49 years. The smallest and largest lesion lenghts were 0.4 and 2 cm, respectively. Seven lesions had developed in the head and neck region, while 2 were in the trunk One of our cases was a 45-year old female patient with a malignant trichoblastoma presented with a lesion in the right side of the lower lip. Conclusion: Trichoblastomas are rare tumors that affect both sexes equally and are seen most commonly in the head and neck region. Recurrence rates were found to be low when they were treated with negative surgical margins.
Keywords: Skin Neoplasms; Plastic Surgery; Histopathology; ADNEXAL NEOPLASM; RARE